Some species of Parmotrema (Parmeliaceae) from the Brazilian Amazon with salazinic acid - Fabiana Aparecida Rego Ciecoski; Flávia Rodrigues Barbosa; Marcelo Pinto Marcelli; Bianca Regina da Hora (Hoehnea)
ABSTRACT Six new species of Parmotrema (P. aristidesii, P. hypoflavum, P. marjorieanum, P. marlitonii, P. nelihondae, and P. subcristiferum) and P. cristiferum, all containing salazinic acid, were collected from the Amazon rainforest in Mato Grosso State, Brazil, (Central South America), and are described, illustrated, and commented by using the ultimate version of the GEL (Lichenological Studies Group) descriptive protocol, that has explained its most important recent improvements.